Chapter A sedimentological pattern of a coastal transitional environment: from the Eastern Mediterranean Sea shoreline through the Lake Bafa - Yalamaz, Burak (Proceedings e report, 2020)
This study represents the lithological correlation of multi-cores taken from the various parts of the current Lake Bafa basin, BAF35, - 37 - 39 - 41, - 42, - 46. Concerning the main depositional characteristics, we reconstructed fundamental characteristics of local abrupt and gradual environmental fluctuations. The gradual changes reflect four main environmental phases are lacustrine stage (last 0.8 ky), lagoon stage (0.8-1.75 ky BP), marine-river interaction stage (1.75-2.7 ky BP) and the earliest marine-dominated stage (>2.7 ky BP).